Fatigue induced by repeated maximal efforts is specific to the rugby task performed - Morel, B.; Rouffet, D. M.; Bishop, D. J.; Rota, S. J.; Hautier, C. A. (International Journal of Sports Science and Coaching, 2015)
The aim of this study was to analyze fatigue occurrence during the repetition of rugby union specific tasks. Eight high-level rugby players (age 23 ± 1.1 y; body mass 90.9 ± 9.8 kg; height 1.83 ± 7.3m) performed three sessions, in a random order, to investigate specific rugby union tasks (Scrum, Maul and Running sprints). Each session consisted in 5 repetitions of 5-s maximal exertion interspersed with 20-s passive recoveries. The scrums were performed into a fixed yoke, while the mauls were realized into a moving yoke. Forces were recorded during the scrums and speeds were monitored during both mauls and sprints. Performance decrease was calculated and complemented by EMG recordings of the vastus lateralis, blood lactate accumulation and rating of perceived exertion (RPE) were also obtained. The repetition of Scrums, Mauls and Sprints induced a decrease in the performance of respectively 23.3 ± 5.3%, 12.6 ± 2.5 % and 7.3 ± 0.9 %. The EMG level decreased only after Scrums and Mauls (respectively 20.8 ± 3.2 % and 12.6 ± 2.5 %; p < 0.0001) while blood lactate accumulation was significantly higher for Sprints (9.2 ± 1.1 mmol.L-1; p = 0.0061) and Maul (8.8 ± 0.8 mmol.L-1; p = 0.0028) compared to Scrum (2.9 ± 1.2 mmol.L-1). Average RPE was higher during the repetition of Scrums (7.8 ± 0.6) compared to Mauls (7.2 ± 0.6; p = 0.0086) and Sprints (7.1 ± 0.5; p = 0.001). The repetition of scrums led to a greater fatigue linked to activation perturbation while during sprints the fatigue was lower and associated with a great metabolic activity. The mauling task showed intermediate characteristics: the fatigue was moderate and both EMG losses and lactate accumulation were substantial. This confirms that conditioning, testing and substitutions should differ according to the players` position in modern rugby.